2022
DOI: 10.3390/jmse10121986
|View full text |Cite
|
Sign up to set email alerts
|

On Formulae for Wave Transmission at Submerged and Low-Crested Breakwaters

Abstract: Submerged and low-crested breakwaters are nearshore barriers with an underwater or slightly emergent crest, designed to reduce the energy of wave attacks and, consequently, to protect the coast from erosion and flooding. Their performance in reducing the wave energy can be evaluated by the value of the wave transmission coefficient, which thus requires accurate prediction. In the last few decades, several experimental investigations allowed the development of several formulae to predict this coefficient that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…For the total number of all 115 data measurements, RMSE calculated was equal to a quite satisfactory value of 0.08. Despite the fact that various data sets of Kt values for submerged structures are mentioned in [3], for the small profile SPBs investigated in this study (narrow crested, homogenous, statically stable rubble-mound and steep sloped trapezoidal bars of a relative depth F/d approximately between 0.10 and 0.25 for up to average wave exposure) and especially for irregular waves, such data were limited. Thus, the need for the experiments framing Despite the fact that various data sets of K t values for submerged structures are mentioned in [3], for the small profile SPBs investigated in this study (narrow crested, homogenous, statically stable rubble-mound and steep sloped trapezoidal bars of a relative depth F/d approximately between 0.10 and 0.25 for up to average wave exposure) and especially for irregular waves, such data were limited.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…For the total number of all 115 data measurements, RMSE calculated was equal to a quite satisfactory value of 0.08. Despite the fact that various data sets of Kt values for submerged structures are mentioned in [3], for the small profile SPBs investigated in this study (narrow crested, homogenous, statically stable rubble-mound and steep sloped trapezoidal bars of a relative depth F/d approximately between 0.10 and 0.25 for up to average wave exposure) and especially for irregular waves, such data were limited. Thus, the need for the experiments framing Despite the fact that various data sets of K t values for submerged structures are mentioned in [3], for the small profile SPBs investigated in this study (narrow crested, homogenous, statically stable rubble-mound and steep sloped trapezoidal bars of a relative depth F/d approximately between 0.10 and 0.25 for up to average wave exposure) and especially for irregular waves, such data were limited.…”
Section: Discussionmentioning
confidence: 94%
“…Several attempts on predicting K t for single submerged porous breakwaters based on various data sets have been carried out. Existing formulae' reviews summarizing them and assessing their accuracy can be found in the literature [2][3][4]. Also, a few studies (e.g., [5,6]) addressed multiple trapezoidal structures.…”
Section: Introductionmentioning
confidence: 99%
“…Wave transmission at coastal structures has been studied by a large number of researchers (e.g. Sollitt and Cross, 1972;Daemen, 1991;d'Angremond et al, 1996;Seabrook and Hall, 1998;Bleck and Oumeraci, 2001;Calabrese et al, 2002;Briganti et al, 2003;Van der Meer et al, 2005;Van Oosten et al, 2006;Koutandos et al, 2006;Buccino and Calabrese, 2007;Makris and Memos, 2007;Panizzo and Briganti, 2007;Goda and Ahrens, 2008;Tomasicchio et al, 2011;Metallinos et al, 2016;Mahmoudi et al, 2017;Lokesha et al, 2019;Brancasi et al, 2022;Le Xuan et al, 2022;Kurdistani et al, 2022;. For a discussion of the various wave transmission studies see the latter two studies.…”
Section: Wave Transmissionmentioning
confidence: 99%
“…Factors such as wave height, period, incident angle, and spectrum characteristics will affect the force and stability of the block. Large waves and long-period waves may exert a greater dynamic load on the block, increasing the displacement and overturning risk of the block [42]. Therefore, this paper mainly starts with the wave, which is the main influencing factor, and meanwhile identifies the position and postural variation of breakwater armor blocks, which has achieved the effect of exploring the stability of breakwater fender blocks.…”
Section: Affect Block Support and Displacementmentioning
confidence: 99%